2018
DOI: 10.3904/kjim.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characteristics of pulmonary sarcomatoid carcinoma

Abstract: Background/AimsPulmonary sarcomatoid carcinoma (PSC) is a poorly differentiated non-small cell lung cancer (NSCLC) that contains components of spindle or giant cells. Owing to its low prevalence, there are insufficient data regarding its clinical features, therapeutic strategies and prognosis.MethodsThe medical records of 26 patients diagnosed with PSC from January 2009 to June 2015 were reviewed and analyzed for clinicopathological characteristics, treatment modality, and outcomes.ResultsThe median age was 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Variable HR 95% CI P-value HR 95% CI P- cell carcinoma, pleomorphic carcinoma and carcinosarcoma. Previous reports demonstrated that pleomorphic carcinoma was a common histological subtype (1,3,21,22). The WHO 2015 lung cancer classification (14) reported that the least common subtype of PSC is pulmonary blastoma (23), which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Variable HR 95% CI P-value HR 95% CI P- cell carcinoma, pleomorphic carcinoma and carcinosarcoma. Previous reports demonstrated that pleomorphic carcinoma was a common histological subtype (1,3,21,22). The WHO 2015 lung cancer classification (14) reported that the least common subtype of PSC is pulmonary blastoma (23), which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Pulmonary sarcomatoid carcinoma (PSC) is a rare type of non-small cell lung cancer (NSCLC) composed of poorly differentiated cells and sarcoma or sarcomatoid components (spindle and/or giant cells) (1). PSC accounts for 0.3-1.0% of all lung cancer cases (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…28-8 and SP263 primary antibodies. Sim et al 126 showed high levels of PD-L1 in 8 out of 13 PSC (61.5%) and Yvorel et al 127 analogously reported high expression of PD-L1 (clone E1L3N, Cell Signaling Technology) in 75% of 36 PSC. In the series of Kim et al 129 PD-L1 and PD-L2 were highly expressed in PSC (90.2%; 37/41 and 87.8%; 36/41), respectively.…”
Section: Psc and Immunotherapymentioning
confidence: 95%
“…In PSCs, several reports have investigated the expression of PD1 and/or PD-L1 to envisage a possible use of these therapies in this setting. 101,[123][124][125][126][127][128][129][130][131][132][133] Although widely employed and approved from different national drug agencies, 123 PD-L1 expression is an imperfect predictive biomarker for immunotherapy in lung cancer. PSC tends to show high levels of immunohistochemical expression with PD-L1, even if it is quite difficult to compare the data so far reported in literature in this histology.…”
Section: Psc and Immunotherapymentioning
confidence: 99%
“…Pleomorphic carcinoma consists of poorly differentiated adenocarcinoma, squamous cell carcinoma, or large cell carcinoma containing at least 10% spindle and/or giant cells or a carcinoma comprised only of spindle and giant cells [11]. For tumors containing a wide range of cellular components, pleomorphic carcinoma is the most common subtype of sarcomatoid carcinomas [12].…”
Section: Discussionmentioning
confidence: 99%